Memahami Peran Psikologi Pendidikan Bagi Pembelajaran - Sakerebau, Junier (BIA, 2018)
Educational psychology as a science that examines the problems of the soul and psychological activity of a person in relation to education as an interaction is a discipline that is quite important in examining the problems that interfere with or support the psyche of students in the learning process, so that through understanding the mental state of students then the teacher can set and try to find a solution to the problem, so for this matter, it is fitting for a teacher to need to have comprehensive knowledge about the psychology of education so that learning can take place effectively and directed. AbstrakPsikologi pendidikan sebagai ilmu yang meneliti masalah jiwa dan aktivitas psikologis seseorang dalam kaitannya dengan pendidikan sebagai interaksi adalah disiplin yang cukup penting dalam memeriksa masalah yang mengganggu atau mendukung jiwa siswa dalam proses pembelajaran, Sehingga dengan memahami keadaan mental siswa maka guru dapat mengatur dan berusaha mencari solusi atas masalah tersebut, sehingga untuk hal ini, sepatutnya seorang guru perlu memiliki pengetahuan yang komprehensif tentang psikologi pendidikan sehingga pembelajaran dapat berlangsung efektif dan terarah.